2009
DOI: 10.1124/mol.109.056259
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species-Dependent Activation of Bax and Poly(ADP-ribose) Polymerase-1 Is Required for Mitochondrial Cell Death Induced by Triterpenoid Pristimerin in Human Cervical Cancer Cells

Abstract: Naturally occurring triterpenoid compounds have long been used as anti-inflammatory, antimalarial, and insecticidal agents. It has become evident that some of the natural or synthetic triterpenoids have promising clinical potential as both a therapeutic and chemopreventive agent for cancer. However, the molecular basis for the antitumor activity of triterpenoid has yet to be defined. In this study, we show that pristimerin, a natural triterpenoid, induces mitochondrial cell death in human cervical cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 38 publications
5
60
0
Order By: Relevance
“…The redundant metastatic signals by different activated GPCRs simultaneously drive the migration of breast cancer cells, which makes the inhibition of breast cancer metastasis by a GPCR-specific inhibitor unfeasible. Ideally, simultaneous 1 can inhibit tumor cell proliferation by inhibiting the NF-κB pathway and cell cycling (Boire et al, 2005;Costa et al, 2008;Yang et al, 2008;Byun et al, 2009;Tiedemann et al, 2009). In addition, prestimerin has been reported to induce caspase-dependent apoptosis of breast cancer cells (Wu et al, 2005) and prostate cancer cells in vitro (Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The redundant metastatic signals by different activated GPCRs simultaneously drive the migration of breast cancer cells, which makes the inhibition of breast cancer metastasis by a GPCR-specific inhibitor unfeasible. Ideally, simultaneous 1 can inhibit tumor cell proliferation by inhibiting the NF-κB pathway and cell cycling (Boire et al, 2005;Costa et al, 2008;Yang et al, 2008;Byun et al, 2009;Tiedemann et al, 2009). In addition, prestimerin has been reported to induce caspase-dependent apoptosis of breast cancer cells (Wu et al, 2005) and prostate cancer cells in vitro (Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact mechanism of HCV-induced Bax activation remained to be elucidated. Meanwhile, a possible link between ROS and Bax activation has been reported (Buccellato et al, 2004;Byun et al, 2009;D'Alessio et al, 2005;Nie et al, 2008). Increasing evidence has suggested that c-Jun NH 2 -terminal kinase (JNK) plays a role in Bax-mediated apoptosis by regulating the function of Bim (Lei & Davis, 2003;Okuno et al, 2004;Putcha et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that pristimerin has promising clinical potential as both a therapeutic and chemopreventive agent for various types of cancer such as pancreatic cancer, glioma, leukemia, cervical cancer, prostate cancer and breast cancer (6)(7)(8)(9)(10)(11). Pristimerin has been shown to induce cell death via a number of several mechanisms, including proteosome inhibition, caspase activation, inhibition of cell cycle progression, and suppression of antiapoptotic nuclear factor kappa B (NF-κB) and Akt signaling pathways (6,9). In breast cancer, it has been reported that pristimeirin induces apoptotic cell death in MDA-MB-231 breast cancer cells in a caspase-dependent manner (11).…”
Section: Introductionmentioning
confidence: 99%